PETITIONS IN CRIMINAL AND CIVIL PROCEEDINGS: COMPARISON - SHARIPOVA Aliya Rashitovna (Правовое государство: теория и практика, 2023)
The «cross-cutting» institutions of criminal, civil, arbitration and administrative procedures are not always universal and identical. Despite terminological coincidences and generally similar notions of petitions in different types of proceedings, the places they occupy in criminal and civil proceedings are different. Purpose: to determine the balance of petitions and applications in criminal procedures, on the one hand and in civil, arbitration and administrative procedures, on the other hand. The determining method of the study is the method of comparative law. In addition, general and special methods (analysis and synthesis, logical, special-legal) are applied. Results: the criminal procedure concept of petitions includes heterogeneous appeals of law enforcement agencies to the court and requests addressed to these bodies by the participants in the pre-trial stages of proceedings, which have no analogues in civil procedure and «classic» petitions of the parties before the court. In criminal procedure, in contrast to arbitration, administrative and civil procedures, petitions many times prevail over applications.